TENCON 2011 - 2011 IEEE Region 10 Conference 2011
DOI: 10.1109/tencon.2011.6129303
|View full text |Cite
|
Sign up to set email alerts
|

Basic study of occurrence frequency of bowel sounds after food ingestion

Abstract: The human bowel produces bowel sounds characteristic of digestive activity. The changes in digestive activity of the bowel are reflected in the frequency and intensity of peristaltic action, and indirectly in variation in bowel sound. Approaching this process in reverse, we detected changes in bowel sound to capture variation in digestive activity of the bowel, aiming to develop a quantitative monitoring technique to trace the cause of the bowel sound variation back to a difference in consumed foods, to compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They then added a wavelet filter to their scheme, improving the overall results; a detection ratio (sensitivity) of 99% with <2% false positives was achieved [ 59 ]. Sakata et al also showed that BS recordings are a source of patients’ stress [ 60 ] and that lifestyle changes may influence BS more than types of food [ 61 ]. They also demonstrated that the frequency of low and normal intensity BS did only correlate to periods of digestion [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…They then added a wavelet filter to their scheme, improving the overall results; a detection ratio (sensitivity) of 99% with <2% false positives was achieved [ 59 ]. Sakata et al also showed that BS recordings are a source of patients’ stress [ 60 ] and that lifestyle changes may influence BS more than types of food [ 61 ]. They also demonstrated that the frequency of low and normal intensity BS did only correlate to periods of digestion [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The long-term bowel sound measurement/analysis system consists of a multi-channel sound sensor sited on an abdominal surface, a data logger (amplifier and A/Dconverter), and a PC for recording and analysis. The analytical method of recorded bowel sound data is same as the procedure adopted in the precedent study [1], [3], [4] and is shown in Fig. 1.…”
Section: Methods Of Measurement and Analysismentioning
confidence: 99%
“…The main advantages of MEMS sensors include compact size, low power consumption, easy integration, and so on. It is of interest that MEMS microphones (silicon microphones) have been used for bowel sound monitoring in some recent studies [32][33][34][35][36] due to their small size and high sensitivity. Wang et al [32] developed a flexible, wearable wireless system using silicon microphone, which could realize long-term, real-time monitoring and analysis of bowel sounds.…”
Section: Introductionmentioning
confidence: 99%